EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) DAN TWO STAY TWO STRAY (TSTS) PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL DITINJAU DARI GAYA BELAJAR SISWA KELAS VIII SMP SE-KABUPATEN REMBANG TAHUN PELAJARAN 2015/2016 - Proborini, Ellen; Mardiyana, Mardiyana; Subanti, Sri (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract: The objective of this research was to investigate the effect of the learning model on learning achievement viewed from studentsâ learning style. The learning models compared were TGT, TSTS and direct learning. The population of this research was the students in grade VIII of state junior high schools in Rembang year 2015/2016. The hypothesis test used unbalanced two way analysis of variance. The results of the research were as follow. 1) TGT and TSTS learning model gave equal students achievement, the students achievement that given TGT was better than direct learning, and the students achievement that given TSTS was better than direct learning. 2) The auditory students achievement was better than visual, but the auditory and kinesthetic have equal students achievement, and visual and kinesthetic have equal students achievement, 3) In TGT, auditory and kinesthetic have equal students achievement, auditory and visual have equal students achievement, and kinesthetic students achievement was better than visual. In TSTS, the auditory and visual have equal students achievement, auditory and kinesthetic have equal students achievement, and visual students achievement was better than kinesthetic. In direct learning, the auditory and visual have equal students achievement, the auditory and kinesthetic have equal students achievement, and kinesthetic and visual have equal students achievement, 4) In auditory, TGT and TSTS learning model gave equal students achievement, wether TSTS and direct learning gave equal students achievement, and TGT and direct learning gave equal students achievement. In visual, students achievement that given TSTS was better than TGT, wether TGT and direct learning gave equal students achievement, and TSTS was better than direct learning. In kinesthetic, students achievement that given TGT was better than TSTS, wether direct learning and TGT gave equal students achievement, and direct learning and TSTS gave equal students achievement.Key words: TGT, TSTS, Direct Learning, Learning Style.